1980
DOI: 10.1007/bf00279711
|View full text |Cite
|
Sign up to set email alerts
|

F1 hybrid versus 32 selected F7 lines performance of common winter wheat (Triticum aestivum ssp. vulgare)

Abstract: One F1 common wheat hybrid ('Zlatna Dolina' x 'Primépi') which had exhibited significant heterosis in a previous study was compared with 32 F7 lines selected from the same cross. The yield test was planted in the 1976-1977 season at two locations: Zagreb, Yugoslavia (optimal environment) and Hutchinson, Kansas, USA (stress environment). The purpose of this experiment was to determine if a homozygous segregant superior to the F1 hybrid could be obtained from the same cross combination.Heading date, plant height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Where more comprehensive studies on heterosis in wheat have taken place, it has been concluded that the best hybrids can outyield the leading varieties, but the yield advantage may not be commercially exploitable (Johnson, 1977(Johnson, , 1978 . In Yugoslavia the best hybrid selected in a twelve-parent diallel cross, grown as spaced plant over a period of four years, showed a 32% heterosis in GY per plant (Jost & Hayward, 1980 Edwards et al ., (1980) found yield advantage of 10-14% above the leading standard cultivar . However, this estimate was obtained at a very low mean yield level (28 .81 q/ha) .…”
Section: Discussionmentioning
confidence: 99%
“…Where more comprehensive studies on heterosis in wheat have taken place, it has been concluded that the best hybrids can outyield the leading varieties, but the yield advantage may not be commercially exploitable (Johnson, 1977(Johnson, , 1978 . In Yugoslavia the best hybrid selected in a twelve-parent diallel cross, grown as spaced plant over a period of four years, showed a 32% heterosis in GY per plant (Jost & Hayward, 1980 Edwards et al ., (1980) found yield advantage of 10-14% above the leading standard cultivar . However, this estimate was obtained at a very low mean yield level (28 .81 q/ha) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the levels of heterosis for wheat yield under stress conditions such as low fertility and late planting date were higher than those under non-stress condition such as high fertility and optimum planting date (Narula, 1984). It has been widely reported that levels of heterosis were influenced by the environments in which the hybrids were grown (Griffing & Zsiros, 1971;Gritton, 1975;Jolt & Hayward, 1980). The expression of heterosis was affected not only by natural factors but also by crop management such as plant density (Severson & Rasmusson, 1968;Uddin, 1991).…”
Section: Levels Of Heterosismentioning
confidence: 99%
“…This material has been evaluated in randomised complete block designs, the elementary plot surface being 4 m 2 . Globally, heterosis appears for yield (on average the 34 hybrids yield 3.1% more grain than their best-parent yield; and the best hybrid yields 7.3% more than the best line), biomass production, and 1 000 seed weight (fig 1, (Briggle et al, 1964;Akemine et Kumagai, 1966;Bitzer et (Briggle et al, 1964;Briggle et al, 1967;Planchon et Diehl, 1967;Jost et Hayward, 1980) (Rousset, 1986;Glenn, 1987 1978, 1980, 1981, 1982 et 1985, à (Nettevich, 1968;Jost et Hayward, 1980 (Bingham, 1983;Lucken, 1986;LefortBuson, 1986;Rousset, 1986) (1987,1988 (Triboi et al, 1985;Triboi, 1986 (Borghi et al, 1988), 7,3% pour 17 hybrides (Brears et al, 1988), 5,9% et 3,6% pour respectivement 61 et 430 hybrides (Morgan et al, 1989 …”
mentioning
confidence: 99%